Intellectual capital and asset quality in an emerging banking market - Nicholas Asare; Margaret Momo Laryea; Joseph Mensah Onumah; Michael Effah Asamoah (Asian Journal of Accounting Research, 2020)
This study examines the causal relationship between intellectual capital and asset quality of banks in Ghana.Using annual data extracted from audited financial statements of 24 banks from 2006 to 2015, a ratio of non-performing loans to gross loans and advances is employed to estimate asset quality growths while the value-added intellectual coefficient by Pulic (2008, 2004) measures intellectual capital. The panel-corrected standard errors estimation technique is used to estimate panel regressions with asset quality as the dependent variable.Asset quality of banks in Ghana is generally not affected by intellectual capital. However, when intellectual capital is divided into its components, the study indicates that there are significant positive relationships between asset quality and two components of intellectual capital. Thus, structural capital and human capital efficiencies positively affect the asset quality of banks.The findings of the study implore managements of banks to increase structural and human capital investments and efficiencies to improve asset quality. Furthermore, the results have direct implications on developments in financial markets in emerging economies.The study analyses the link between typical intellectual capital and asset quality of banks which is yet to be empirically examined in an emerging banking market.